Effect of Bakers Yeast on Growth and Nutrient Utilization in Crossbred (Large White Yorkshire X Desi )Pigs - Sekar M (Department of Animal Nutrition, College of Veterinary and Animal Sciences, 2003)
A study was carried out to assess the influence of baker's yeast culture on growth performance, digestibility of nutrients and carcass characteristics in Large White Yorkshire x Desi (75:25) crossbred pigs. Thirty weaned piglets (15 barrows and 15 gilts) with an average body weight of 13.5 kg were divided into three homogeneous groups with regard to age, sex and body weight. Ten piglets in each group were randomly distributed into five replicates of two piglets each. The three groups were randomly allotted to three dietary treatments viz., T,- control (standard ration), Tr control diet supplemented with 0.25 per cent baker's yeast culture and T3- control diet supplemented with 0.5 per cent baker's yeast culture. The piglets were fed on their respective grower rations which contained 18 per cent crude protein and 3200 kcal digestible energy per kg until they attained an average body weight of 50 kg and thereafter changed to finisher rations which contained 14 per cent crude protein and 3 100 kcal digestible energy per kg until the pigs were slaughtered. A digestibility trial was conducted towards the end of the experiment using chromic oxide as external indicator. On completion of seven months of age six pigs from each treatment were slaughtered to study the carcass characteristics. Average daily gain of 352, 383 and 405 g were recorded for the groups T" T2 and T3, respectively. The pigs fed with diet containing 0.5 per cent baker's yeast (T3) had higher (P<0.05) average daily gain than those fed with unsupplemented diet (T,). But, there was no significant difference between T, and T2 as well as T2 and T3. However, there was a trend for a higher average daily gain for those fed 0.25 per cent yeast culture (T2) over those fed control diet Cl (T,). Feed conversion efficiency was 4.36, 4.05 and 3.83 for the groups T" T2 and T3, respectively. The pigs fed with diets containing 0.25 (T2) and 0.5 per cent baker's yeast (T3) had higher (P<O.O 1) feed conversion efficiency than those fed with unsupplemented diet (T,). The digestibility coefficient for dry matter and ether extract were significantly higher (P<0.05) for pigs fed 0.5 per cent yeast